Participation in rural community groups and links with psychological well-being and resilience: a cross-sectional community-based study. Issue 1 (December 2016) - Lyons, Anthony; Fletcher, Gillian; Farmer, Jane; Kenny, Amanda; Bourke, Lisa; Carra, Kylie; Bariola, Emily
Abstract Background Fostering the development of community groups can be an important part of boosting community participation and improving health and well-being outcomes in rural communities. In this article, we examine whether psychological well-being and resilience are linked to participating in particular kinds of rural community groups. Methods We conducted a household survey involving 176 participants aged 18 to 94 years from a medium-sized rural Australian town. We gathered data on psychological well-being (Warwick-Edinburgh Mental Well-being Scale), resilience (Brief Resilience Scale), and the types of community groups that people participated in as well as a range of characteristics of those groups, such as size, frequency of group meetings, perceived openness to new members, and whether groups had leaders, defined roles for members, hierarchies, and rules. Results Univariable regression analyses revealed significant links between particular group characteristics and individual psychological well-being and resilience, suggesting that the characteristics of the group that an individual participates in are strongly tied to that person's well-being outcomes. Multivariable analyses revealed two significant independent factors. First, psychological well-being was greatest among those who participated in groups without a hierarchy, that is, equal-status relationships between members. Second, resilience was greater among those who reported having a sense of influence within a group. Conclusions Our findings suggest that policymakers wishing to promote participation in rural community groups for health and well-being benefits may do well to encourage the development of particular characteristics within those groups, in particular equal-status relationships and a sense of influence for all group members.